Game Online Genshin Impact Sebagai Media Komunikasi Antar Budaya - Rizki Ahmalina Putra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research tries to see how the position of online games as a medium of intercultural communication, in terms of benefits, positive and negative. In this study the writer used a qualitative descriptive research method, where the writer will describe how the game is used as a medium to communicate with people of different cultures. The description of this game is done by comparing it with how social media applications work in general. The results of the study show that the Genshin Impact game can be used as a medium to interact with people from different cultural backgrounds.